CARTOON SEMIOTIC ABOUT MARCH OF RETURN IN THE PALESTINIAN NEWSPAPERS: : (A Comparative Analytical Study) - Issa, Talat A. Hamid (ALBAHITH ALALAMI, 2019)
This study aims to reveal the semiotic of “March of Return” cartoon in the Palestinian journalism, topics, Symbols and semantics that were covered. This study is descriptive. It uses the survey method. Content analysis, and methodological comparison was also used. The researcher chose an intentional sample of Palestine and Al-Hayat Al-Jadida newspapers for one year from March 30, 2018 to March 31, 2019, through a comprehensive inventory of all cartoons of the return marches during this period, which amounted to 59 cartoons. The study has reached the following findings: Newspapers cartoons focused on the topics of durability of the protesters, then clashes with a clear margin, then the topics of repression and Israeli attacks on the participants in the marches. The cartoons focused on the unnamed symbolic characters far more than the real ones. The two newspapers described the characters as positive in general for the Palestinian ones, and negative for the rest of the characters, especially the Israelis. The aim of spreading the spirit of hope and durability came first in the two newspapers, followed by the goal of showing pain and suffering, and then show the brutality of the occupation. The most prominent symbols in the cartoons were Palestinian. It focused on the Palestinian flag, the Palestinian Koffia, and the symbols of the return marches such as burning balloon, and burning kites, while Israeli symbols focused on the barbed wall, star of David, and the military machines of the occupation.